Form, Counterpoint, and Meaning in a Fourteenth-Century French Courtly Song - Leach, E (Oxford University Press, 2012)
This chapter presents an analysis of Guillaume de Machaut's balade De petit po (B18). Taking an understanding of medieval counterpoint as its starting point, the analysis treats the two central contrapuntal voices first before examining the response to these voices provided variously by the (mutually exclusive) triplum and contratenor parts. Ultimately the analysis inflects a consideration of the balade's performance contexts, which serve as a means of simultaneously presenting and commentating on its verbal text.